Hydrogen peroxide degradation of bleaching systems with different trays: Randomized clinical trial - Mailart, Mariane Cintra [UNESP]; Ferracioli, Carolina de Siqueira [UNESP]; Gomes Torres, Carlos Rocha [UNESP]; Palo, Renato Miotto [UNESP]; Borges, Alessandra Buhler [UNESP] (Mosher & Linder, Inc, 2020)
Purpose: This crossover study evaluated the hydrogen (HP) and carbamide (CP) peroxide degradation of bleaching gels in prefilled (PT) and customized trays (CT). Methods: Volunteers were randomly allocated to treatments (n=10): PT-HP/OGO (Opalescence GO-10%); CT-HP/WTC (White Class-10%) or CT-CP/OPF (Opalescence PF-10%). Gel samples were collected from the upper and lower trays in each period (baseline, 15, 30, 50 and 120 minutes). HP concentration was determined with the potassium permanganate titration method. Degradation was calculated based on initial concentration of gels. Repeated measures two-way ANOVA and Tukey's test (5%) were applied. Results: Bleaching gels exhibited exponential degradation over time. In 30 minutes, no significant differences in degradation among them were detected (P= 0.13). After 2 hours, lower degradation of CT-CP/OPF (61.85 +/- 10.65), compared with hydrogen peroxide in PT and CT (71.55 +/- 8.24 and 78.69 +/- 9.33, respectively) was observed. The gels showed higher degradation rate in lower trays than in upper trays in all evaluated times. In general, the bleaching gels in lower trays degraded more than in upper trays. The carbamide peroxide gel presented lower degradation than hydrogen peroxide after 2 hours. The degradation of the 10% hydrogen peroxide gel used in prefilled trays was higher than the one in customized trays after 30 minutes, but after 120 minutes, the degradation rate was similar for both.